Causes of death in patients with autoimmune and rheumatic diseases-a 16-year autopsy-based study - Marta Juliana Mantilla; Juan José Chaves; Juan Camilo Santacruz; Gustavo Rodríguez-Salas; Igor Rueda; Ana Maria Santos; John Londoño; Julio Cesar Mantilla (University of São Paulo, 2023)
Introduction: the autopsy is an essential medical procedure; however, its use has declined over the decades. In autoimmune and rheumatological diseases, anatomical and microscopic diagnosis is critical to diagnose of the cause of death. For this reason, our objective is to describe the cause of death in patients diagnosed with autoimmune and rheumatic diseases who underwent an autopsy in a Pathology reference center in Colombia. Materials and methods: a retrospective and descriptive study of autopsy reports. Results: between January 2004 and December 2019, 47 autopsies of patients with autoimmune and rheumatological diseases were performed. Systemic lupus erythematosus and rheumatoid arthritis were the most common diseases. The leading cause of death was related to infections, being opportunistic infections in the majority of the cases. Conclusions: our autopsy-based study was focused on patients with autoimmune and rheumatological conditions. Infections are the leading cause of death, particularly opportunistic infections, diagnosed mainly by microscopy. Thus, the autopsy should continue to be considered the "gold standard" to determine the cause of death in this population.